Analisis Kesuksesan Website Stikom Library dengan Menggunakan Model DeLone dan McLean Berdasarkan Persepsi Mahasiswa Institut Bisnis dan Informatika Stikom Surabaya - Widya, Laras Tilottama; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Library of the Institute of Business and Information Stikom Surabaya (Surabaya Stikom) has website. Stikom Library website is a digital library of Stikom Surabaya with system online that was released in 2008. Stikom Library website Surabaya ranks to 2,839 in Indonesia, according to Alexa Uniform Resource Locator (URL) www.alexa.com. After Stikom Library website has never been implemented evaluation of system quality, information quality and service quality of Stikom Library website by the end user perception as feedback to the organizer website.By success analysis of the Stikom Library website as an evaluation and input or consideration for the libraries Stikom Surabaya in knowing the system quality, information quality and service quality. Analysis of the success of this method of information system success DeLone and McLean by analyzing the variables of System Quality, Information Quality, Service Quality, Use, User Satisfaction, and net benefit of Stikom Library website. Results of research by distributing questionnaires on a sample of 198 college students, showed that the System Quality variable positive and significant impact to User Satisfaction. Variable Service Quality has a positive and significant impact on use. Variable User Satisfaction Using positive and significant impact on Net Benefit. And the variable Service Quality had a significant influence on Net Benefit variables through mediating variables User Satisfaction. Stikom Library Surabaya should further improve the information related to library services and systems Stikom Library website.